2021
DOI: 10.1208/s12249-021-02151-2
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion Complexes of Daidzein with Cyclodextrin-Based Metal–Organic Framework-1 Enhance Its Solubility and Antioxidant Capacity

Abstract: Daidzein, an aglycone-type isoflavone, is useful in the prevention of atherosclerotic cardiovascular diseases. However, the solubility of daidzein remains relatively low even with pharmaceutical interventions (e.g., γ-cyclodextrin inclusion complex). In the present study, daidzein-cyclodextrin-metal organic framework solid dispersion complexes were prepared by the solvent evaporation method. The physicochemical properties of the complex and its effect on the solubility of daidzein were evaluated. The enhanceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…CDs also increase the antioxidant activity of other biologically active compounds. Daidzein–CD–metal organic framework solid dispersion complexes prepared by the solvent evaporation method increased daidzein DPPH scavenging activity ~1.3 times [ 67 ]. In another study, DPPH radical-scavenging activity test indicated that the caffeic acid complexes with α-CD and with β-CD obtained by the ground mixture method had greater antioxidant activity than caffeic acid; additionally, greater results were obtained for the complex with α-CD [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…CDs also increase the antioxidant activity of other biologically active compounds. Daidzein–CD–metal organic framework solid dispersion complexes prepared by the solvent evaporation method increased daidzein DPPH scavenging activity ~1.3 times [ 67 ]. In another study, DPPH radical-scavenging activity test indicated that the caffeic acid complexes with α-CD and with β-CD obtained by the ground mixture method had greater antioxidant activity than caffeic acid; additionally, greater results were obtained for the complex with α-CD [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 H– 1 H NOESY NMR measurements were performed to investigate the detailed intramolecular interactions of FD (SAC/αCD), FD (SAC/βCD), and FD (SAC/γCD) in solution (Figures – ). The 1 H– 1 H NOESY NMR measurement was used to infer the relative position of the inclusion complex because it can confirm the interaction between the guest molecule and the CD cavity . In FD (SAC/αCD), a cross peak was confirmed between the peak Hc (2.90 ppm) derived from the alkyl group (H) of SAC and the peak H-6 (3.75 ppm) derived from αCD (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H− 1 H NOESY NMR measurement was used to infer the relative position of the inclusion complex because it can confirm the interaction between the guest molecule and the CD cavity. 24 In FD (SAC/αCD), a cross peak was confirmed between the peak Hc (2.90 ppm) derived from the alkyl group (H) of SAC and the peak H-6 (3.75 ppm) derived from αCD (Figure 10b). Furthermore, a cross peak was confirmed between Ha (5.06 ppm) and Hb (5.69 ppm) of SAC and H-3 (3.81 ppm) and H-5 (3.66 ppm) derived from αCD (Figure 10c).…”
Section: Determination Of Inclusion Molar Ratio Between Sac and α β γ...mentioning
confidence: 88%
“…Numerous pharmacological effects of DAI include anti-carcinogenesis [ 42 ], anti-inflammatory [ 43 ], antioxidant [ 44 ], anti-diabetic [ 45 ], cholesterol-lowering [ 46 ], and cardiovascular activity [ 47 , 48 ].…”
Section: Mechanism Of Action and Pharmacological Applications Of Daid...mentioning
confidence: 99%